How Do Trait-Mediated Non-lethal Effects of Predation Affect Population-Level Performance of Mosquitoes? - Chandrasegaran, Karthikeyan; Juliano, Steven A. (Frontiers in Ecology and Evolution, 2019)
Non-lethal, trait-mediated effects of predation impact prey behaviour and life-history traits. Studying how these effects in turn influence prey demography is crucial to understand prey life-history evolution. Mosquitoes are important vectors that claim several million lives every year worldwide by transmitting a range of pathogens. Several ecological factors affect life-history traits of both larval and adult mosquitoes, creating effects that cascade to population-level consequences. Few studies have comprehensively explored the non-lethal effects of predation and its interactions with resources and competition on larval, adult, and population traits of mosquitoes. Understanding these interactions is important because the effects of predation are hypothesised to rescue prey populations from the effects of density-dependence resulting from larval competition. Aedes aegypti larvae reared at two different larval densities and subjected to three non-lethal predator treatments were monitored for survival, development time, and adult size through the larval stages to adult eclosion, and adult females were monitored for survival and reproduction through their first gonotrophic cycle. Intraspecific competition increased larval development time, yielded small-bodied adults, and interacted with predator treatments to impact fecundity. Exposure to cues from a living predator affected both body size and latency to blood feed in females. Analysis of life-table traits revealed significant effects of competition on net reproductive rate (R0). The interaction between competition and predator treatments significantly affected the cohort rate of increase (r) and the index of performance (r’). The index of performance, which estimates rate of population change based on the size-fecundity relationship, was significantly and positively correlated with r, but overestimated r slightly. Lack of significant effect of predator treatments and density on cohort generation time (Tc) further suggests that the observed effects of treatments on r and r’ were largely a consequence of the effects on R0. Also, the significant effects of treatment combinations on larval development time, adult body size and fecundity were ultimately manifested as effects on life-table traits estimated from adult survival and reproduction.